Genotypic variation in the ability of landraces and commercial cereal varieties to avoid manganese deficiency in soils with limited manganese availability: is there a role for root‐exuded phytases?. Issue 3 (25th February 2014) - George, Timothy S.; French, Andrew S.; Brown, Lawrie K.; Karley, Alison J.; White, Philip J.; Ramsay, Luke; Daniell, Tim J.
Abstract The marginal agricultural‐systems of the Machair in the Western Isles of Scotland often have limited micronutrient availability because of alkaline soils. Traditional landraces of oats, barley and rye are thought to be better adapted to cope with the limited manganese (Mn) availability of these soils. When commercial cultivars are grown on the Machair, limited Mn‐availability reduces crop yield and quality. We hypothesised that traditional cereal landraces selected on the Machair acquire Mn more effectively and that this could be linked to exudation of phytase from roots which would release Mn complexed with inositol phosphates. Growth and Mn‐acquisition of five landraces and three commercial cultivars of barley and oats were determined in Machair soil. In addition, root phytase activities were assayed under Mn‐starvation and sufficiency in hydroponics. In Machair soil, landraces had greater capacity for acquiring Mn and a greater ability to achieve maximum yield compared to the commercial cultivars. Under Mn‐starvation, root phytase exudation was upregulated in all plants, suggesting that this trait might allow cereals to acquire more Mn when Mn‐availability is limited. In the landraces, exuded phytase activity related positively to relative Mn‐accumulation, whereas in the commercial cultivars this relationship was negative, suggesting that this trait may be secondary to an efficiency trait that has been lost from commercial germplasm by breeding. This research shows that cereal landraces possess traits that could be useful for improving the Mn‐acquisition of commercial varieties. Exploiting the genetic diversity of landraces could improve the sustainability of agriculture on marginal calcareous lands globally.